Multielemental analysis of 20 mushroom species growing near a heavily trafficked road in Poland - Mleczek, M; Niedzielski, P; Kalač, P; Budka, A; Siwulski, M; Gąsecka, M; Rzymski, P; Magdziak, Z; Sobieralski, K (Environmental science and pollution research international, 2016)
The aim of this work was to compare 10 mostly edible aboveground and 10 wood-growing mushroom species collected near a heavily trafficked road (approximately 28,000 vehicles per 24 h) in Poland with regard to their capacity to accumulate 26 trace elements (Ag, Al, As, Au, B, Ba, Bi, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, Li, Mn, Ni, Pb, Re, Sb, Se, Sr, Te, Tl, and Zn) in their fruit bodies in order to illustrate mushroom diversity in element accumulation. All analyses were performed using an inductively coupled plasma optical emission spectrometry (ICP-OES) spectrometer in synchronous dual view mode. The aboveground species had significantly higher levels of 12 elements, including Ag, As, Pb, and Se, compared to the wood-growing species. An opposite relationship was observed only for Au, Ba, and Sr. The results of principal component analysis (PCA) and hierarchical cluster analysis (HCA) implied some new relationships among the analyzed species and elements. Of the analyzed mushroom species, lead content in Macrolepiota procera would seem to pose a health risk; however, at present knowledge regarding lead bioaccessibility from mushrooms is quite limited.
Keywords: Environment; Vegetables; stopové prvky; Mushrooms; monitorování životního prostředí; Transportation; zelenina; Trace Elements; shluková analýza; Trace elements; Contamination; doprava; Environmental Pollutants; Consumer health; Environmental Monitoring; Principal Component Analysis; Agaricales; analýza hlavních komponent; látky znečišťující životní prostředí; Cluster Analysis; Poland; Polsko